Microwave-Assisted Synthesis of Carbon Dot – Iron Oxide Nanoparticles for Fluorescence Imaging and Therapy - Chung, Seokhwan; Zhang, Miqin (Frontiers in Bioengineering and Biotechnology, 2021)
Fluorescence microscopy is commonly used to image specific parts of a biological system, and is applicable for early diagnosis of cancer. Current fluorescent probes, such as organic dyes and quantum dots, suffer from poor solubility and high toxicity, respectively, demonstrating a need for a colloidal stable and non-toxic fluorescent probe. Here we present an iron oxide and carbon dot (CD) based nanoparticle (CNPCP) that displays optical properties similar to those of conventional fluorescent probe and also exhibits good biocompatibility. Fluorescent CDs were synthesized from glucosamine onto chitosan – polyethylene glycol (PEG) graft copolymer using microwave irradiation. These NPs were monodispersed in aqueous environments and displayed excitation-dependent fluorescence; they demonstrated good size stability and fluorescence intensity in biological media. In vitro evaluation of CNP as fluorescent probes in cancer cell lines showed that these NPs caused little toxicity, and allowed fast and quantitative imaging. Model therapeutic doxorubicin (DOX) was conjugated onto the NPs (CNPCP-DOX) to demonstrate the multifunctionality of the NPs, and in vitro studies showed that CNPCP-DOX was able to kill cancer cells in a dose dependent manner. These results indicate the potential of using CNPCPs as fluorescent probes capable of delivering chemotherapeutics.